Analisis Teori Kemampuan, Motivasi Kerja, Kepuasan Kerja terhadap Kinerja Perawat - devia lydia putri; Budi Hartono (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2018)
Performance is influenced by ability, work motivation, job satisfaction. Some explained in Rivai's theory (2005) ; Bittel, L.R and Nestrom, J.W (1991) ; Gibson (2001) ; Usman (2008), where the common problems faced by organizational leaders. The right nursing process activities have not been carried out adequately by the nurses, which has an impact on the hospital occupancy rate. The high turnover data in 2017 was 18% compared to 2016 as much as 12%. This study uses an analytical survey with a quantitative approach, using a cross sectional design, this population is 89 people, in this study researchers used the entire population to be sampled. Data analysis method Partial Least Square (PLS). The results showed that the variable Ability of Gibson's theory (2001) was able to explain as much as 90,8% (goodness of fit), and the remaining 9,2% could be found by indocators / variables outside the theory under study. Maslow's Work Motivation Variable (1943) is able to explain 80,1% (goodness of fit), and the remaining 19,9% can be found indicators / variables outside the theory under study. Nurse Performance Variables theory of Mondy and Noe (1990) ; Tsui, et, al. (1997) ; L. Mathis and John H. Jackson (2002) ; Simamora (2004) is able to explain 86,6% (goodness of fit), and the remaining 13,2% can be found indicators / variables outside the theory under study. Overall performance is influenced by ability and motivation, but job satisfaction has no effect. It is recommended that the hospital be carried out efforts to increase capacity, namely the ability to interact, conceptual abilities, and technical abilities, while for work motivation, namely physical, sense of security, compassion, self actualization and appreciation.